Nová role hemu ve zdraví a nemoci - hemové senzorové proteiny - Martínková, Markéta (Chemické listy, 2022)
The iron atom possesses unique properties, being manifested in the heme molecule. In addition to the involvement of heme in many processes (such as oxygen or electron transport and catalysis of enzyme reaction), it can also regulate key pathways critical for health. Heme-containing sensor proteins mediate the heme regulation role. The review aims to underline the main characteristics of the heme-containing sensor proteins group, either sensing heme or sensing a gas molecule through a heme-binding site, on the example of specific representatives from each sensor subgroup.
Keywords: hemoproteiny; Heme; hem; lidé; Hemeproteins; Humans